Pengaruh Kualitas Pelayanan, Harga, Promosi, Lokasi Terhadap Kepuasan Pelanggan Puspita Laundry Palembang - M Rafli Pasha; Idham Cholid (Universitas Multi Data Palembang, 2026)
This study aims to determine the effect of service quality, price, promotion, and location on customer satisfaction at Puspita Laundry Palembang. This study uses a quantitative approach. The sampling technique used is non-probability with purposive sampling, and the number of samples in this study is 128 Puspita Laundry customers. Hypothesis testing was conducted using multiple linear regression analysis through the SPSS version 25 program. Based on the partial test results, it shows that Service Quality, Price, Promotion, and Location have a positive and significant effect on Customer Satisfaction. Meanwhile, simultaneously, the results of the study show that Service Quality, Price, Promotion, and Location together have a significant effect on the Customer Satisfaction of Puspita Laundry Palembang.